STRATEGI PENGEMBANGAN SOFT SKILLS PADA PEMBELAJARAN TEMATIK DI MIN TANJUNGSARI, KEBUMEN - Barohinul Umam, Faiz (El-Hamra, 2018)
The background of this research is that soft skills is one of the most important aspects in achieving success that needs to be instilled early on, especially through formal education institutions. MIN Tanjungsari is a school that develops soft skills through thematic learning. Soft skills are communication, emotional, language, group skills, have ethics and morals, courtesy and communication skills. Thematic learning is learning that integrates several subjects in one theme.The strategy for developing soft skills is to integrate soft skills attributes through appropriate strategies and methods in thematic learning. Learning design must be effective and efficient. The results of this study indicate that thematic learning is able to develop students' soft skills in the form of communication, honesty and cooperation.Key Words: Soft Skills, Thematic Learning